SHIFTS IN MICRORNA EXPRESSION PROFILES WITHIN SKELETAL MUSCLE AND ADIPOSE ACROSS THE LIFESPAN. (11th November 2018) - Benard, T; Parnell, L; Lessard, S; Fielding, R; Rivas, D
Abstract: A blunted response to anabolic stimuli (ie. muscle contraction) is a characteristic feature of aging skeletal muscle, a phenomenon termed "anabolic resistance". We and others have previously shown a critical role for the small non-coding RNA molecules, microRNA (miRNA), in anabolic resistance. While current investigations have identified age-associated change in miRNA profiles within anabolic tissue they have been limited in scope of ages across the lifespan. Male C57BL/6 mice aged 6, 18, 24 and 30 months (n=6/group) were anesthetized and underwent a single-leg high-frequency electrical stimulation contraction (HFES) protocol while the opposite limb served as the surgical sham control (SHAM). One hour following HFES, muscle and epididymal adipose were collected. 752 distinct miRNA were quantified using miRCURY LNA miRNA miRNome PCR Panels. miRNA differentially expressed across age groups underwent bioinformatics miRNA-mRNA pathway analysis via DIANA-miRPath v3.0 to identify pathways targeted as a function of age. Subsequently, TarBase v8.0 and TargetScanMouse 7.1 analyses were performed to assess the predictive strength and species conservation of miRNA-mRNA interactions. Contraction-induced transcription of skeletal muscle miRNA appears to be blunted significantly with aging. However, in skeletal muscle, the Thyroid Hormone Signaling pathway appears to be increasingly targeted with significant increases in miR-25/32/92/363/367 and Let-7-5p miRNA families and miR-143/145 cluster expression in aging. Similarly, adipose-derived miR-9/155/146a expression, regulators of NF-kB activity, was significantly upregulated with age. The determination of dysregulated miRNA expression profiles in these two metabolically active tissues may help explain the muscular anabolic blunting and pro-inflammatory environment characteristic of aging.